2006
DOI: 10.1021/cm061999d
|View full text |Cite
|
Sign up to set email alerts
|

New Tungsten(VI) Guanidinato Complexes:  Synthesis, Characterization, and Application in Metal−Organic Chemical Vapor Deposition of Tungsten Nitride Thin Films

Abstract: Two new tungsten complexes, [W(NtBu) 2 (NMe 2 ){(iPrN) 2 CNMe 2 }] (2) and [W(NtBu) 2 (H){(iPrN) 2 CNMe 2 }] (3), as precursors for metal-organic chemical vapor deposition (MOCVD) of tungsten nitride thin films were synthesized from the starting compound [W(NtBu) 2 (Cl){(iPrN) 2 CNMe 2 }] (1) by substitution of the chloro ligand by a dimethylamido and a hydrido group, respectively. Compounds 1-3 were characterized by 1 H NMR, 13 C NMR, EI-MS, IR, and elemental analysis including single-crystal X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Films deposited during WN_2 and WN_4, which consist of WN material, show resistivity values between $500 and 1100 mV cm. These values are comparable to the lowest values reported for WN thin films grown by MOCVD [20,24,25]. The resistivity increased at higher deposition temperature which could be attributed to increased crystallinity and grain size that possibly increases electron scattering along grain boundaries.…”
Section: Resistivitysupporting
confidence: 84%
See 2 more Smart Citations
“…Films deposited during WN_2 and WN_4, which consist of WN material, show resistivity values between $500 and 1100 mV cm. These values are comparable to the lowest values reported for WN thin films grown by MOCVD [20,24,25]. The resistivity increased at higher deposition temperature which could be attributed to increased crystallinity and grain size that possibly increases electron scattering along grain boundaries.…”
Section: Resistivitysupporting
confidence: 84%
“…Amido–imido complexes of tungsten such as [W(N t Bu) 2 (NH t Bu) 2 ] and [Cl 4 (RCN)W(NR′)] (R = CH 3 , Ph; R′ = i Pr, C 3 H 5 , Ph) have been used as MOCVD precursors under single source precursor (SSP) conditions or in combination with NH 3 as reactive gas for the deposition of WN thin films. Earlier, we demonstrated that all nitrogen coordinated amidinato‐based tungsten complexes [W(N t Bu) 2 {( i PrN) 2 CMe} 2 ] and guanidinato‐based tungsten compounds like [W(N t Bu) 2 (NMe 2 ){( i PrN) 2 CNMe 2 }] and [W(N t Bu) 2 (H){( i PrN) 2 CNMe 2 }] can serve as potential precursor for the deposition of WN thin films in a home built CVD reactor .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid incorporation of halide or carbon atoms inside the films a new class of all nitrogen coordinated, mixed imido-amido-complexes of molybdenum, like [Mo(N t Bu) 2 (NEt 2 ) 2 ] (9) and [Mo(N t Bu) 2 (NMe 2 ) 2 ] (10), were developed and tested as precursors for the MOCVD of Mo x N y . In the past we have shown, that it is possible to design volatile, all nitrogen coordinated tungsten-complexes by introducing chelating guanidinato-ligands which have been successfully used as precursors for the MOCVD of tungsten nitride thin films (11,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…WF 6 ) a number of precursors have been developed. 11, 12 The compounds a Department of Chemistry, Materials Chemistry Centre, University College London, 20 2 ], 16 and [W(N t Bu) 2 R{h 2 -( i PrN) 2 CNMe 2 }] (R = NMe 2 , H), 17 have been employed in either CVD or ALD processes, often in the presence of ammonia, affording films of tungsten nitride or tungsten carbonitride. The tungsten imido compounds, [W(=NR)Cl 4 (R¢CN)] (R = i Pr, Ph, C 3 H 5 ; R¢ = Me, Ph) were used in an (AA)CVD process with hydrogen in the carrier gas stream.…”
Section: Introductionmentioning
confidence: 99%